Investigation of the Properties of Fresh Concrete with Scoria as Coarse Aggregates. - Erugu, Pius (Kabale University, 2023)
The properties of fresh concrete have been studied by various researchers but knowledge gaps still exist concerning the workability of fresh concrete. This is because the workability of concrete cannot be studied using any single method as it involves many aspects to be investigated like slump, setting time, flow-ability, among others. By investigating the properties of fresh concrete namely; setting time, yield stress, slump, density and air content, this research work will aid the utilisation of concrete with scoria as coarse aggregates in the construction industry of Uganda and elsewhere it has not been utilised on the globe. This research will experimentally be significant in determining the most suitable values of slump for fresh concrete with scoria as coarse aggregates prior to its casting on construction site. In this project, the slump, yield stress and density will be further analysed basing on the experimental results obtained in the laboratory in relation to the findings by early researchers and conclusions will be drawn. The equations relating yield stress, slump and setting time of concrete obtained by early researchers; Hu et al (1996), Ferraris and de Lerrard (1998) and Murata and Kikukawa (1992) will be compared in relation to the values of slump that will be obtained in my experimental findings and the suitable equation(s) for computing yield stress of concrete with scoria as coarse aggregates will be recommended.